INTERNAL TRIBAL CONFLICT IN THE REGENCY OF TANAH DATAR IN THE REFORM ERA - Yanti Mulia Roza (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The purpose of this tribal research is to identify patterns of internal conflict in Tanah Datar District, which is located in three sub-districts. The method used is qualitative descriptive analysis with historical and sociological approaches. The primary sources were interviews with indigenous groups; LKAAM, KAN (Kerapatan Adat Nagari), MTKAAM (High Council for Natural Density Minangkabau), chiefs of the two conflicting parties, chairman of the MUI, Alim Ulama in nagari, secondary sources; books, articles and journals. Data analysis using constant comparative analysis method (grounded theory research). In the reform era, the struggle for the title of sako is not only to get tribal heritage and dignity, but is influenced by political needs and prestige.